Late Pleistocene Geology and Paleolithic Archaeology of the Shimaki Site, Hokkaido, Japan. Issue 3 (1st April 2014) - Buvit, Ian; Izuho, Masami; Terry, Karisa; Shitaoka, Yorinao; Soda, Tsutomu; Kunikita, Dai; Buvit, Ian; Carson, Mike T.
<x xml:space="preserve">Abstract</x> Here, we assess geochronological, sedimentological, stratigraphic, and stone tool data from Shimaki, an Upper Paleolithic site in southeastern Hokkaido, Japan. Overall, we find that Shimaki's landscape context and flaked‐stone assemblage are similar to sites in Hokkaido that date to just before or at the Last Glacial Maximum (LGM). Based on several numerical ages, we suggest that the artifact‐bearing layer, including a wedge‐shaped core morphologically similar to post‐LGM specimens from Siberia, formed during the LGM, and sites like Shimaki with clear stratigraphy, relatively undisturbed cultural material, and what appear to be transitional artifact forms, may be key to answering questions about the origins of microblades, but, without human fossil remains for ancient DNA comparison, are inadequate to address the fate of Late Pleistocene Siberians.